2021
DOI: 10.30564/jams.v4i1.2728
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Role of Vitamin D in Systemic Lupus Erythematosus

Abstract: Vitamin D is a hormone precursor with multiple biological effects. It binds to vitamin D receptors on target cells. It is an important participant in the metabolism of calcium and phosphorus in vivo. It is closely related to cell cycle, cell proliferation, differentiation, apoptosis, signal transduction and immune regulation. Its role in the treatment of infection, tumor and even immune diseases has been gradually recognized and studied. Patients with systemic lupus erythematosus generally have decreased level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Studies have shown that patients with SLE have elevated serum IFN-α levels, which correlate with disease activity and severity, [40] and biologics targeting type I IFN bring new possibilities for the treatment of SLE. [41] Early studies have found that the ability of macrophages to clear apoptotic cell debris in SLE patients is defective, [42] and recent studies have shown that abnormal activation or interference in the coordination of immune response between monocytes and macrophages will lead to and aggravate immune dysregulation. [43] Neutrophils are involved in the process of inflammation and infection and are an important component of the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with SLE have elevated serum IFN-α levels, which correlate with disease activity and severity, [40] and biologics targeting type I IFN bring new possibilities for the treatment of SLE. [41] Early studies have found that the ability of macrophages to clear apoptotic cell debris in SLE patients is defective, [42] and recent studies have shown that abnormal activation or interference in the coordination of immune response between monocytes and macrophages will lead to and aggravate immune dysregulation. [43] Neutrophils are involved in the process of inflammation and infection and are an important component of the innate immune system.…”
Section: Discussionmentioning
confidence: 99%